Droughts in future climate change in the UK - Rahiz, M (2013)
This thesis seeks to investigate the changes in the characteristics of 20th and 21st century meteorological droughts in the UK to address the following lines of inquiry: 1) How credible are rainfall-based indices in representing hydrological droughts, 2) How coherent are droughts?, 3) Can alternative method of analysis provide new (or additional) information on the uncertainties in climate models?, and 4) Will future drought characteristics change?. Key results, respectively, are summarized as follows: • The drought severity index (DSI), can be considered a good proxy for assessing hydrological droughts as can be seen in its ability to capture the major hydrological events. The main caveat of the DSI is that there is often an underestimation of drought intensity and duration, • Drought covariance is higher for the (i) wet season, (ii) moderate and (iii) shorter duration droughts, • Evaluating climate models using drought statistics produces contrasting results compared with that using the model's precipitation fields. Drought statistics show biases which are largely negative, more intense, and have a greater spatial coverage. • The projected ensemble-mean change is generally greater (and more widespread) for (i) moderate droughts and (ii) wet season compared with extreme droughts and the dry season, respectively with increases in drought intensity, drought covariance index, frequency of drought months and frequency of drought events for a given duration shown for England.